Diana Markosian: Santa Barbara - Markosian, Diana; Myles, Lynda (New York : Aperture, 2020)
"Diana Markosian's Santa Barbara brings together staged scenes, film stills, and family pictures in an innovative and compelling hybrid of personal and documentary storytelling. In 1996, following the collapse of the Soviet Union, Markosian's mother, Svetlana, placed a classified ad in a Los Angeles newspaper: "I want to see America, and meet a kind man who can show me the country," she wrote. One man who responded was from Santa Barbara, California, and their correspondence led to Svetlana becoming a mail-order bride, fleeing her increasingly dreary prospects in post-Soviet Moscow with seven-year-old Markosian and her older brother in tow. This book is a retelling of the family's first years in the US, imagined as an episode from the soap opera Santa Barbara-the first American show allowed on Russian television in the 1990s. For many families, including Markosian's, this soap opera symbolized the opportunities of America and the West; for her project, Markosian wrote a script in collaboration with one of the original Santa Barbara writers and hired actors to reenact moments from her personal history. A major exhibition of this work, including a three-channel film presentation, will open at Rencontres d'Arles in July 2020, in advance of a fall 2020 exhibition at the San Francisco Museum of Modern Art"-- Provided by publisher.
boek
Keywords: Markosian, Diana